DIATOM AND SEDIMENTARY RECORD DURING THE MID-HOLOCENE EVOLUTION OF THE SAN BLAS ESTUARINE COMPLEX, NORTHERN PATAGONIA, ARGENTINA (Ameghiniana, 2012)
Abstract. Diatom and sedimentological analyses of two cores from San Blas Bay and the analysis of historical charts provide information about the environmental evolution of this estuarine complex during the last 5000 yr BP. The Holocene sea-level regression is recorded in San Blas Bay by infilling of a tidal channel. Two sediment cores were drilled at Arroyo Jabalí (San Blas Bridge) and at the former inlet of Arroyo Walker and Arroyo Jabalí (Paso Seco). The diatom record of the San Blas Bridge sequence is dominated by marine and brackish/freshwater plankton and tychoplankton and composed by fine to very fine sand and mud characterizing the infilling of a tidal channel. The Paso Seco sequence is more abundant in sand. Textural and diatom facies are interpreted as the infilling of a tidal channel very similar to the one at San Blas Bridge, that evolved towards the top into a sandflat characterized by the dominance of marine and marine-brackish epipsammon accompanied by marine tychoplankton. Arroyo Walker and Arroyo Jabalí were flowing eastward across a tidal channel during the Holocene. Because of obstruction of the channel, the tidal channel assemblages were replaced by sandflat assemblages. According to historical charts, as late as 1833 a tidal inlet still existed in this sector, which was later obstructed completely according to Twentieth Century charts. At this timescale, eustasy is considered to be a minor environmental control on the dynamics of the system. Instead, control is forced by other factors, such as inlet instability due to morphological changes of the sand barrier whether emergent or submerged.Resumen. REGISTRO DIATÓMICO Y SEDIMENTARIO DE LA EVOLUCIÓN DEL COMPLEJO ESTUARINO SAN BLAS DURANTE EL HOLOCENO MEDIO, PATAGONIA NORTE, ARGENTINA. El análisis de las diatomeas y la sedimentología de dos testigos obtenidos en la Bahía San Blas, y la comparación de cartas náuticas, han aportado información sobre la evolución ambiental de este complejo estuarino durante los últimos 5000 años AP. El relleno de canales de mareas representa la regresión marina del Holoceno en la Bahía San Blas. Se obtuvieron dos testigos, en el arroyo Jabalí (Puente San Blas) y en la antigua desembocadura de los arroyos Walker y Jabalí (Paso Seco). El registro diatómico de la secuencia Puente San Blas está dominado por plancton y ticoplancton marino y salobre/dulceacuícola y compuesto por arena fina a muy fina y fango, caracterizando el relleno de un canal de mareas. Los registros diatómicos y sedimentarios de la secuencia Paso Seco se interpretan como la colmatación de un canal de mareas muy similar a la secuencia de Puente San Blas, que evolucionó hacia una planicie arenosa en el tope, caracterizada por epipsammon marino y marino-salobre acompañado por ticoplancton marino. Durante el Holoceno, los arroyos Walker y Jabalí desaguaban hacia el este, a través de un canal de mareas. El proceso de obstrucción del canal (enPaso Seco) hizo que las asociaciones características de canales de mareas fueran reemplazadas por las típicas de planicies arenosas. De acuerdo a cartas antiguas, en 1833 aún existía una desembocadura de mareas en este sector, que se obstruyó completamente según cartas del Siglo XX. En ese momento, la eustasia habría sido un factor de control ambiental menor en este sistema. Un factor importante es la inestabilidad de la desembocadura debida a cambios morfológicos de la barrera medanosa emergida o sumergida.